KNOWLEDGE OF PRIMARY SCHOOL TEACHERS ON RECOLONIZATION OF PUPILS AT RISK OF CHILD ABUSE IN KANO URBAN NIGERIA. - ABUBAKAR MOHAMMED JIBO; ADAMU MOHAMMED (Ntec Specialist, 2011)
Background: Child abuse continues to draw the attention of world health leaders because of its various consequences. Prevention of child abuse is a collective responsibility. This responsibility is even more among those who work with children such as teachers, doctors, nurses, and social workers. Method: A descriptive cross-sectional study was conducted using systematic sampling technique, sampling interval was determined, and 270 respondents were chosen for the study. We assessed the knowledge of primary school teachers on child abuse in Kano municipal LGA, Kano state. Results: Teachers that attended training on child abuse were shown to have a statistically significant higher knowledge of child abuse than those who did not attend training on child abuse (p = 0.04). No significant difference was observed when the respondents' sexes, qualification, previous training on child abuse as well as duration of their career as teachers was compared (p = 0.05). The teachers' perception on child abuse was found to be fair with close to half (45.4%) agreeing positively to responses on perception of what constitute a child abuse. The result showed that more than 87% of the teachers were able to identify one or more forms of child abuse. More than half of the respondents 180(69.8%) assessed have poor general knowledge of child abuse. However, knowledge of prevention of child abuse was found to be fair among 50% of the teachers. Only previous training on child abuse was found to influence knowledge of the respondents on preventing child abuse. Conclusion: The study found out that the knowledge of teachers to be below average in all aspects of child abuse. Hence, there is need for government to adequately train teachers on child abuse so that they will be equipped with adequate knowledge for them to be able to identify, intervene and prevent child abuse among school children